THE EFFECT OF THE STUDENT ACTIVE LEARNING (SAL) TYPE COOPERATIVE LEARNING MODEL ON THE CREATIVE THINKING ABILITIES OF GRADE IV STUDENTS ON THE MATERIAL OF CHANGES IN THE FORM OF OBJECTS - Ghoniyah, Dzuqqotul; Roheni; Merakati, Indah (Jurnal Ilmu Pendidikan Dasar (JIPDA), 2026)
This study aims to determine the effect of the cooperative learning model type Student Active Learning (SAL) on the creative thinking ability of fourth-grade elementary school students. The background of this research is based on the importance of fostering creative thinking skills so that students can generate varied, original, and detailed ideas during the learning process. This research employed a quantitative approach using a Quasi-Experimental Design. The sample consisted of two classes: class IVA as the experimental group, which received learning through the SAL model, and class IVB as the control group, which used conventional learning. The instruments used were a creative thinking ability test and an observation sheet for learning implementation. The results showed that the implementation of the SAL model reached 95% in each meeting, categorized as very good. The average pretest score in the experimental class increased from 16.47 to 58.08 on the posttest, while the control class increased from 27.94 to 42.35. The N-Gain analysis showed an average of 0.503 (medium category) for the experimental class and 0.202 (low category) for the control class. The Independent Sample t-test result showed a Sig. (2-tailed) value of 0.000 < 0.05, indicating a significant effect of the SAL model on students’ creative thinking skills. Thus, the SAL model positively stimulates fluency, flexibility, originality, and elaboration while fostering an active, creative, and collaborative learning atmosphere.